Modern trends in management of the budget system - Bitoleuova, Yerkezhan; Aibossynova, Dina; Kabdullina, Gulmira; Baimukhasheva, Manshuk; Tazhibaeva, Raikhan (Serbian Journal of Management, 2020)
The article deals with the pressing issues of the development of local self-government in the Republic of Kazakhstan at the current stage. The feature of the reforms, currently underway, is the strengthening of financial independence of local self-government bodies. First of all, it is attributed to the introduction of the independent budget at the local self-government level. The study brings into the light the systemic nature of the budget process and analyses the world’s best reformation practices for the budget process. The systematic approach helps reveal the distinguishing characteristics of budget decision making in the context of costly and programme-targeted planning models. It also allows investigating the business climate adequately and finding optimal paths for development. The results from this research involve the aspects and significance of the management of the budget system of the Republic, on the basis of which the relevant conclusion has been drawn.